(untitled) (International Journal of Health, Animal Science and Food Safety, 2016)
Cow and buffalo milk and camel milk were analyzed and compared for processing related parameters. The average heat stability of cow, buffalo and camel milk samples analyzed was 1807.4 seconds, 1574.6 seconds and 133.6 seconds respectively at 140 °C. Thus, the heat stability of camel milk was significantly lower than the cow milk and buffalo milk. The average rennet coagulation time (RCT) of cow, buffalo and camel milk was 310.6 seconds, 257.4 seconds and 604.2 seconds respectively. Thus, RCT of camel milk was significantly higher than the cow milk and buffalo milk. The camel, cow and buffalo milk samples showed negative alcohol stability. The rate of acidity was increased propositionally with time in camel milk with no curd formation and weaker body.